Anatolii Volodymyrovych Skorokhod (short biographical essay) - Kadyrova, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
This paper was originally written in English and published in EUROPEAN MATHEMATICAL SOCIETY. Newsletter 94, December 2014. Below is a shorter version of the paper in Ukrainian; translated by M.I. Portenko.